Normalize this! human rights, resistance and hip-hop - Hussain, Syeda Re'em (AUC Knowledge Fountain, 2013)
Born in the United States as the Civil Rights Movement (CRM) was dying out; Hip-Hop as a language and social milieu presented itself as a voice from and to the street, at a time that the street needed a critical voice. As a construct of five elements- Emceeing, DJing, B-Boying, Graffiti and Knowledge; Hip-Hop provided the movement with a narrative that was both critical of itself as well as critical of the legal liberal method it employed. Concentrating on the CRM in the 1960s to date; the aim of this paper is to build upon an already existing voice within International Law (IL). That is both critical to the liberal rights discourse and wary of its dominance in resistance movements, in an effort to highlight places outside traditional IL discourse that both resists and uses a different language, and creates a different milieu for resistance.